Exosome: The “Off-the-Shelf” Cellular Nanocomponent as a Potential Pathogenic Agent, a Disease Biomarker, and Neurotherapeutics - Ghosh, Satyajit; Ghosh, Surajit (Frontiers in Pharmacology, 2022)
Exosomes are nanosized “off the shelf” lipid vesicles released by almost all cell types and play a significant role in cell-cell communication. Exosomes are already proven to carry cell-specific cargos of proteins, lipids, and miRNA, noncoding RNA. These vesicles can be selectively taken up by the neighbouring cell and can regulate cellular functions. Herein we have discussed three different roles of exosomes in neurosciences. Firstly, we have discussed how exosome plays the role of pathogenic agent as a part of cell-cell communication and transmit pathogen like amyloid-beta(Aβ) and help in the propagation of neurodegenerative and other neurological diseases. In the next section, the review talks about the role of exosomes in biomarker discovery in neurological disorders. Towards the end, we have reviewed how exosomes can be harnessed and engineered for therapeutic purposes in different brain diseases. This review is based on the current knowledge generated in this field and our comprehension of this domain.